2020
DOI: 10.3390/pr8091167
|View full text |Cite
|
Sign up to set email alerts
|

Socheongryongtang Modulates Asthma-Related Changes via Modulation of TNF-α and T-bet as well as IFN-γ in an Asthma Murine Model

Abstract: In 2017 the World Health Organization (WHO) reported that 235 million people suffered from asthma, and that 383,000 deaths were due to asthma in 2015. Asthma cannot be completely eradicated and the medications for asthma are associated with many adverse effects. Socheongryongtang is one of the prescriptions which has traditionally been used for the treatment of pulmonary disease, but the anti-asthmatic mechanism is unclear. To investigate the anti-asthmatic mechanism of socheongryongtang, BALB/c mice were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The activated Th2 cells release high level of cytokines, including IL-4, IL-5, and IL-13, leading to trigger AHR, induce mast cells, infiltrate eosinophils into the lungs, and subsequently increase mucus secretion [ 48 ]. Several studies reported that the expression of TNF- α , TGF-b, IL-1B, and α -SMA genes is significantly increased in OVA-induced asthma in animals, which is consistent with our findings [ 13 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…The activated Th2 cells release high level of cytokines, including IL-4, IL-5, and IL-13, leading to trigger AHR, induce mast cells, infiltrate eosinophils into the lungs, and subsequently increase mucus secretion [ 48 ]. Several studies reported that the expression of TNF- α , TGF-b, IL-1B, and α -SMA genes is significantly increased in OVA-induced asthma in animals, which is consistent with our findings [ 13 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…[99][100][101] Simultaneously, DEX mitigated inflammation by reducing serum and lung levels of TNF. 102,103 Thus, the TNF inhibitor provides promise concerning improved asthma symptoms. 96 Our data demonstrate that ICA significantly diminishes the invasion of inflammatory cells in the airway lumen and reduces the transcript level of Syk, Jak2, Jun and…”
Section: Discussionmentioning
confidence: 99%
“…Anti-IgE agents, such as omalizumab, are immunomodulatory and are called the 'magic bullet' for allergic asthma treatment as they can suppress the exacerbation of asthma [39]. In our lab, we have been concentrating on finding Th2 cell-suppressing agents from natural products [13,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma might be caused by the imbalance of Th1 and Th2 factors [14], and specifically in asthma, Th2-related factors, such as IL-4 and IL-13, increase significantly [13,15]. IL-4 induces GATA-3's transcriptional activity via a positive feedback mechanism and causes enhanced IgE secretion from B cells, eosinophilia, mucous hypersecretion, and airway remodeling [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation